Distensibility and pain of the uterine cervix evaluated by novel techniques. (30th March 2016) - Gregersen, Hans; Hee, Lene; Liao, Donghua; Uldbjerg, Niels
Abstract: The article serves to review the literature on the human uterine cervix based on a new distension technology named functional luminal imaging probe. This technology was originally developed to study the biomechanical competence of the gastro‐esophageal junction where it provides a geometric profile of the lumen during distension, which can be related to sensory data. We searched and reviewed publications on cervical distention from 2002. The functional luminal imaging probe technology has been used for studying the mechanical and mechano‐sensory properties of the cervix in non‐pregnant women. In early pregnant women and in term pregnant women, the technique provides geometric measurements from the whole cervical canal during distension, which changes dramatically during pregnancy. Furthermore, it has been demonstrated that the technique predicts the outcome of labor induction better than the Bishop score does. The functional luminal imaging probe technology has potential as a research tool as well as for clinical use in gynecology and obstetrics.